ANALISIS YURIDIS KEPASTIAN HUKUM PENDAFTARAN TANAH YANG DIBUAT ATAS NAMA ANAK DI BAWAH UMUR DAN PERTANGGUNGJAWABAN WALI - CUT AHMAD RIYADI (PREMISE LAW JURNAL, 2017)
Land is the bounty of God the Almighty which has great benefit so that it becomes the source of the creatures’ live in the world. judicial analysis on legal certainty in land registration by minors and guardian’s custody showed that 1) the position of a minor as a legal subject in registering his land was that age limit or a child who requests for registering since 2015 has been 18 years, according to the Circulation Letter of Agrarian Affairs and Layout/the Head of the National Land Agency No. 4/SE/I/2015 on January 26/;2015 on Age Limit in Land Service. Keyword : Land Registration, Guardian of Minor